Customer service and its’ impact on the satisfaction of account holders: A study of general banking service of United Commercial Bank PLC Tejgaon Branch - Talukder, Shuvojyoti (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.